2017
DOI: 10.1074/jbc.m116.766824
|View full text |Cite
|
Sign up to set email alerts
|

UBE3B Is a Calmodulin-regulated, Mitochondrion-associated E3 Ubiquitin Ligase

Abstract: Recent genome-wide studies found that patients with hypotonia, developmental delay, intellectual disability, congenital anomalies, characteristic facial dysmorphic features, and low cholesterol levels suffer from Kaufman oculocerebrofacial syndrome (KOS, also reported as blepharophimosis-ptosis-intellectual disability syndrome). The primary cause of KOS is autosomal recessive mutations in the gene UBE3B. However, to date, there are no studies that have determined the cellular or enzymatic function of UBE3B. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…For example, the overexpression of HERC4 facilitates the proliferation of hepatocellular carcinoma (HCC), whereas depletion of HERC4 slows down proliferation and increases the apoptotic rate of HCC (Zheng and Shabek, 2017). Knockdown of UBE3B, of one of the 'other HECTs', in glioblastoma cells was shown to cause changes in mitochondrial morphology and physiology and the suppression of cellular proliferation (Braganza et al, 2017). Another study observed NEDD4 upregulation increased cell proliferation, while downregulated NEDD4 in prostate carcinoma cells inhibited colony formation and induced apoptosis (Li et al, 2015).…”
Section: Cell Growth Proliferation and Migrationmentioning
confidence: 99%
“…For example, the overexpression of HERC4 facilitates the proliferation of hepatocellular carcinoma (HCC), whereas depletion of HERC4 slows down proliferation and increases the apoptotic rate of HCC (Zheng and Shabek, 2017). Knockdown of UBE3B, of one of the 'other HECTs', in glioblastoma cells was shown to cause changes in mitochondrial morphology and physiology and the suppression of cellular proliferation (Braganza et al, 2017). Another study observed NEDD4 upregulation increased cell proliferation, while downregulated NEDD4 in prostate carcinoma cells inhibited colony formation and induced apoptosis (Li et al, 2015).…”
Section: Cell Growth Proliferation and Migrationmentioning
confidence: 99%
“…Gels were stained in Coomassie Blue and a single, ∼1 cm gel slice was excised for each sample and submitted for processing. Excised bands were digested with trypsin as previously described (Braganza et al, 2017). Briefly, the excised gel bands were destained with 25 mM ammonium bicarbonate in 50% acetonitrile (ACN) until no visual stain remained and the gel pieces were dehydrated with 100% ACN.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitated samples were shortly separated (1cm) by SDS-PAGE and stained with SimplyBlue™ SafeStain (Thermo Fisher Scientific). The stained gel regions were excised and in-gel trypsin digested as previously described 27 . In brief, the excised gel bands were washed with HPLC water and destained with 50% acetonitrile (ACN)/25mM ammonium bicarbonate until no visible staining.…”
Section: In-gel Trypsin Digestionmentioning
confidence: 99%